KOMUNIKASI KESEHATAN DI MASA PANDEMI COVID-19 (Studi Deskriptif Tentang Persepsi Penerapan Protokol Kesehatan Pengunjung Pasar Sentra Grosir Cikarang) - feri Sanjaya; Dina Sudarmika; Winda Gustina (Oratio Directa (Prodi Ilmu Komunikasi), 2022)
ABSTRACTHealth communication is an activity of delivering health information to make changes in individual and group behavior to improve health.This study aims to determine health communication in the delivery of messages about health protocols, the Market Center wholesale Cikarang.The approach used in this research is qualitative approach with descriptive method.Data collection techniques are carried out through observation,interviews,and documentation.Based on the results of the study, health communication in the delivery of perceptions about health protocols in the Cikarang wholesale Center Market during the pandemic that wearing masks is ineffective because it makes it difficult to breathe, although there are also those who perceive masks as protective so that they are worn in accordance with appropriate health protocols.While hand washing is not done for allergic nreasons, also because it does not come into contact with other visitors.Although there are also those who assess hand washing according nto health protocols needs to be done because it can protect hands from ngerms and corona viruses.Meanwhile, in maintaining distance, market visitors stated that they did not maintain a distance according to health protocols because they perceived it as ineffective considering the narrow market room while visitors were crowded, although there are also those who apply maintaining distance according to health protocols because they come to the market during the day so that it is quiet. Keywords: Health Communication, Public Perception, Health Protocols,Covid-19